2020
DOI: 10.1021/acsabm.0c00534
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropically Conductive Biodegradable Scaffold with Coaxially Aligned Carbon Nanotubes for Directional Regeneration of Peripheral Nerves

Abstract: Fascicular rearrangement of an injured peripheral nerve requires reconnection of nerve sprouts from anterior and Büngner bands from distal sides of the lesion, failing to which leads to inefficient regeneration of the injured nerve. However, existing neural scaffolds have limited neuroregeneration efficiency because of either the lack of alignment of fibers and a conductive second phase, leading to compromised electrical conductivity, or the lack of extracellular matrix components and in vivo validation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…The alignment was achieved effectively only up to 5 wt% of MWCNTs, beyond which they started to agglomerate leading to a rough surface (Sung et al, 2004). Electrospinning could be a good technique to align the CNTs (Namgung et al, 2011) (Ghosh et al, 2020). But through spinning, CNT may align in radial direction instead of linear direction which is not at all required in peripheral neural tissue engineering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alignment was achieved effectively only up to 5 wt% of MWCNTs, beyond which they started to agglomerate leading to a rough surface (Sung et al, 2004). Electrospinning could be a good technique to align the CNTs (Namgung et al, 2011) (Ghosh et al, 2020). But through spinning, CNT may align in radial direction instead of linear direction which is not at all required in peripheral neural tissue engineering.…”
Section: Resultsmentioning
confidence: 99%
“…Injuries of peripheral nerve were classified into neuropraxia, axonotmesis and neurotmesis bySeddon, (1943). Most of the time, PNI can result from acute trauma (road traffic incidents, construction accidents, gunshot wounds), laceration (a cut or tear in the nerve tissue), traction (stretching), compression, severe bruising (contusion), drug injection injury and electrical injury leading to paresthesia (abnormal sensation like tingling), dysesthesia (an unpleasant sensation), hypesthesia (low sensitivity to stimulus), loss of proprioception, numbness, motion abnormality, and even muscle atrophy and dysfunction(Ghosh et al, 2020; Henry, 2014; Menorca et al, 2013; Yi et al, 2019). Sadly, the regeneration or replacement capacity of neuronal tissue is very restricted in adults (Steward et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research aims to provide a means for repair or even circumvention of this damage. Work conducted by Ghosh et al shows that electrospun nanofiber scaffolds containing MWCNTs demonstrated excellent regeneration properties for peripheral nerve cells in rats [109]. The nerve cells regenerated directionally, an important characteristic for functional nerve regeneration.…”
Section: Biomedical Scaffoldsmentioning
confidence: 99%
“…On the other hand, we can explore the combination of anisotropic topographical cues and other biophysical and biochemical cues, like electrical stimuli and bioactive molecules. Some relevant studies have demonstrated promising results regarding in vitro neuron oriented growth and in vivo nerve regeneration [ 160 , [233] , [234] , [235] , [236] ]. To make them transplantable from bench to bedside, a stable power supply and sustained local therapeutic agent release still require optimization.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%